Postawy pro-merytokratyczne a postulaty redukcji nierówności dochodów: Polska na tle innych krajów (2002-2008) = Pro-meritocratic attitudes vs. postulates for reducing income inequality: Poland vs. other countries, 2002-2008 - Słomczyński, Kazimierz Maciej (1943- ) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Theoretical arguments and empirical results presented in the article are aimed at triggering a discussion on socially accepted rules of the division of goods. The model of education meritocracy, based on the assumption that, in the hordes entering the job market, the relation between the level of education and awards for playing professional roles (expressed through wages and prestige) is as close as allowed by distributions of analysed variables.
Keywords: merytokracja; nierówności społeczne; podział dóbr